2002
DOI: 10.1017/s0952836902000596
|View full text |Cite
|
Sign up to set email alerts
|

Attendance patterns of Steller sea lions (Eumetopias jubatus) and their young during winter

Abstract: Winter attendance patterns of lactating Steller sea lions Eumetopias jubatus and their offspring were recorded during the late stages of nursing when the young were expected to move from milk to independent foraging. Trip duration and nursing visits to shore by 24 mothers with pups (7±9 months old) and six mothers with yearlings (19±21 months old) were noted during 600 h of observations (from 22 January to 1 April 1996) at a non-breeding haulout site in south-eastern Alaska. Pups and yearlings tended to stay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
(42 reference statements)
4
48
0
Order By: Relevance
“…2a) by making the standard deviations equal to the reported mean seasonal distance travelled (summer mean = 10 km, winter mean = 133 km; Merrick & Loughlin 1997). We defined the summer breeding season as May to August and the non-breeding season as September to April, a time when all animals of both sexes tend to be distributed across a wider range (Loughlin et al 1987, Merrick & Loughlin 1997, Trites & Porter 2002. We focused our analysis on adult females during the winter because their summer distribution was too constrained to support further analysis at the spatial resolution of our study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a) by making the standard deviations equal to the reported mean seasonal distance travelled (summer mean = 10 km, winter mean = 133 km; Merrick & Loughlin 1997). We defined the summer breeding season as May to August and the non-breeding season as September to April, a time when all animals of both sexes tend to be distributed across a wider range (Loughlin et al 1987, Merrick & Loughlin 1997, Trites & Porter 2002. We focused our analysis on adult females during the winter because their summer distribution was too constrained to support further analysis at the spatial resolution of our study.…”
Section: Methodsmentioning
confidence: 99%
“…Accessibility: As central-place foragers, Steller sea lions regularly rest on land between foraging trips (Merrick & Loughlin 1997, Brandon 2000, Trites & Porter 2002, Milette & Trites 2003. We therefore began with the hypothesis that the at-sea distribution of Steller sea lions is related to the accessibility of the marine environment from the central place (Hypothesis 1; Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming complete dependence, regional differences in pup blubber FA profiles would be a reflection of regional differences in the FA composition of adult female diets that were passed on to offspring through milk (Puppione et al 1996, Iverson et al 2001. However, recent studies of maternal attendance patterns (Trites & Porter 2002) and the dispersal and movement patterns of young SSLs (Loughlin et al 2003, RaumSuryan et al 2004, Fadely et al 2005 have suggested that some individuals may wean during the spring of :1n-11, 20:1n-11 and 20:5n-3; second function accounted for an additional 17.9% of variation and was most influenced by 16:1n-7, 18:1n-9 and 22:6n-3 their first year of life. If this is true, regional differences in the blubber FA profile of pups may also result from regional differences in prey consumption or in the timing of when pups begin to forage independently.…”
Section: Differences In Fa Profiles By Regionmentioning
confidence: 99%
“…Our study aimed to compare previous estimates of juvenile and adult Steller sea lion foraging ecology achieved through scat analysis with our own approximations obtained via stable carbon and nitrogen isotope analyses of blood components from 9 mo old sea lions and potential prey items. Time of weaning is unclear for Steller sea lions, but it is believed to occur gradually between 3 and 24 mo of age as they increasingly augment their mother's milk with solid food (Trites & Porter 2002, Loughlin et al 2003, Raum-Suryan et al 2004). Therefore, the stable isotope values from the blood components of 9 mo old Steller sea lions reflect some combination of milk that reflects their mother's diet and their own opportunistic or intentional prey ingestion.…”
Section: Introductionmentioning
confidence: 99%